Fate of Aneurysmal Common Iliac Artery Landing Zones Used for Endovascular Aneurysm Repair. (October 2015) - Griffin, Claire L.; Scali, Salvatore T.; Feezor, Robert J.; Chang, Catherine K.; Giles, Kristina A.; Fatima, Javairiah; Huber, Thomas S.; Beck, Adam W.
Purpose: To determine outcomes of aneurysmal common iliac arteries (aCIA) used for landing zones (LZs) during endovascular aneurysm repair (EVAR).Methods: This single-center study retrospectively compared 57 EVAR patients (mean age 72±8 years; 56 men) with 70 aCIAs (diameter ≥20 mm) to 25 control EVAR subjects (mean age 73±7 years; 20 men) with 50 normal (≤15-mm) CIA LZs treated consecutively during the same time interval. The CIA LZ measurements were analyzed using random effects linear mixed models to determine diameter change over time. Life tables were used to estimate freedom from endoleak, reintervention, and all-cause mortality.Results: The mean maximum preoperative CIA diameter in the aCIA LZ group was 24.8±4.5 mm (range 20.0–47.3, median 23.9) vs 13.6±1.5 mm (range 9.2–15.0, median 13.9; p<0.001) in the controls. Nineteen aCIA LZs were treated outside the instructions for use of the device. Median follow-up in the aCIAs LZ cohort was 39.2 months [interquartile range (IQR) 15, 61] vs 49.3 months (IQR 36, 61) in the controls (p=0.06). The rate of aCIA LZ change (0.09 mm/mo, 95% CI 0.07 to 0.1) was significantly greater than controls (0.03 mm/mo, 95% CI −0.009 to 0.07; p<0.0001). No type Ib endoleaks developed in either group; however, aCIA LZ patients had 6 (11%) iliac limb–related reinterventions. There were significantly more endograft-related reinterventions in the aCIA LZ patients (n=10, 14%) compared with controls (n=2, 4%; p=0.06). There was no difference in mortality or freedom from any post–hospital discharge endoleak.Conclusion: Aneurysmal CIA LZs used during EVAR experience greater dilatation compared with normal LZs, but no significant difference in outcome was noted in midterm follow-up. However, an increased incidence of graft limb complications or endograft-related reintervention may be encountered. Use of aCIA LZs appears to be safe; however, greater patient numbers and longer follow-up are needed to understand the clinical implications of morphologic changes in these vessels when used during EVAR.